Social determinants of the healthcare needs of undocumented migrants living with non-communicable diseases: a scoping review - Claudine Burton-Jeangros; Yves Jackson; Janeth Tenorio-Mucha; Corinne Jeffries-Tolksdorf; Jan-Erik Refle (BMJ Publishing Group, 2024)
Objectives We aimed to map the social determinants of meeting the healthcare needs of undocumented migrants living with non-communicable diseases (NCDs) throughout their migration journey (from the country of origin to the country(/ies) of transit and destination).Design We conducted a scoping review.Data sources We searched literature in Medline, Embase, Web of Science and Google Scholar.Eligibility criteria We included articles that describe interventions, programmes or policies for undocumented migrants living with cardiovascular diseases, cancer, chronic respiratory disease, or diabetes. There were no restrictions by setting (eg, hospital, community or mobile clinic) or country. We included articles published in English, Spanish, or French between 2000 to 2022.Data extraction and synthesis The data were structured according to the Commission on Social Determinants of Health framework, differentiated along the migration journey (country of origin, transit, departure and integration, and country of destination). A new conceptual model emerged from data synthesis.Results We included 22 studies out of 953 identified articles. They reported data from Italy, the USA, Spain, Switzerland, The Netherlands, France, Austria, and Sweden. They show that individual determinants (material, biological, psychosocial and behavioural) evolve throughout the migration journey and influence healthcare needs. The satisfaction of these needs is conditioned by health system-related determinants such as availability and accessibility. However, the individual and health-system determinants depend on the political and legal context of both the country of origin and the country(/ies) of destination, as well as on the socioeconomic position of undocumented migrants in the destination country.Conclusions Migrant health policies should aim at better responding to NCDs-related healthcare needs of undocumented migrants throughout their migration journey, taking into account the social, economic and legal factors that underlie their health vulnerability.